2014
DOI: 10.1016/j.biopsycho.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The conditioning and extinction of fear in youths: What's sex got to do with it?

Abstract: Adult work shows differences in emotional processing influenced by sexes of both the viewer and expresser of facial expressions. We investigated this in 120 healthy youths (57 boys; 10–17 years old) randomly assigned to fear conditioning and extinction tasks using either neutral male or female faces as the conditioned threat and safety cues, and a fearful face paired with a shrieking scream as the unconditioned stimulus. Fear ratings and skin conductance responses (SCRs) were assessed. Male faces triggered inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Although gender [59] and neuroticism [63] do not appear to be associated with differential conditioning in unaffected youth, several other influential factors have been identified. These include the type of conditioned stimuli [62], contingency awareness [61], attention bias [60], parental clinical psychopathology [64], and youth subclinical psychopathology [65,66]. When examining threat generalization across stimuli, evidence suggests that unaffected youth exhibit greater threat generalization than adults [61,68].…”
Section: Threat Conditioning and Extinction In Unaffected Youthmentioning
confidence: 99%
See 1 more Smart Citation
“…Although gender [59] and neuroticism [63] do not appear to be associated with differential conditioning in unaffected youth, several other influential factors have been identified. These include the type of conditioned stimuli [62], contingency awareness [61], attention bias [60], parental clinical psychopathology [64], and youth subclinical psychopathology [65,66]. When examining threat generalization across stimuli, evidence suggests that unaffected youth exhibit greater threat generalization than adults [61,68].…”
Section: Threat Conditioning and Extinction In Unaffected Youthmentioning
confidence: 99%
“…For example, several reports indicate that extinction is achieved for SCR, FPS, and SR measures among youth [36,57,63,67]; whereas other studies indicate that the CRs persists for SCR and SR measures after extinction [36,58,60,62-64,67]. With regard to examining extinction retention and generalization, 9-10 year olds reported greater SR fear to stimuli resembling the CS+, compared to 5-8 year olds [67].…”
Section: Threat Conditioning and Extinction In Unaffected Youthmentioning
confidence: 99%
“…Importantly, other factors such as sex (Lebron-Milad et al, 2012;Milad et al, 2006Milad et al, , 2010Rosenbaum et al, 2015), gonadal hormones (Merz et al, 2012;Milad et al, 2006), education (Rosenbaum et al, 2015), age (Bellebaum & Daum, 2004;Rosenbaum et al, 2015), ethnicity (Martínez, Franco-Chaves, Milad, & Quirk, 2014;Nelson, Bishop, Sarapas, Kittles, & Shankman, 2014), personality traits (Otto et al, 2007), and genetic factors (Åhs, Frick, Furmark, & Fredrikson, 2014;Hettema, Annas, Neale, Kendler, & Fredrikson, 2003;Hindi Attar, Finckh, & Büchel, 2012;Klucken et al, 2014;Lonsdorf et al, 2009;Merrill, Steinmetz, Viken, & Rose, 1999;Wendt et al, 2015) have also been shown to modulate conditionability. Importantly, it is common for fear conditioning studies to exclude participants due to poor evidence of a conditioned SCR (Chauret et al, 2014;Milad, Orr, Pitman, & Rauch, 2005;Oyarzún et al, 2012;Phelps, Delgado, Nearing, & LeDoux, 2004;Spring et al, 2015). The percentage of exclusions reported varies across studies and can go from 4% (Chauret et al, 2014) up to 19% (Oyarzún et al, 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, it is common for fear conditioning studies to exclude participants due to poor evidence of a conditioned SCR (Chauret et al, 2014;Milad, Orr, Pitman, & Rauch, 2005;Oyarzún et al, 2012;Phelps, Delgado, Nearing, & LeDoux, 2004;Spring et al, 2015). The percentage of exclusions reported varies across studies and can go from 4% (Chauret et al, 2014) up to 19% (Oyarzún et al, 2012. The exclusion of participants is usually based on very small SCRs to the unconditioned stimulus (US), that is, the unconditioned response (UCR), or to a given number of CS+ trials during conditioning.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, two other studies found no impact of hormonal differences in fear extinction learning on SCR [ 25 , 30 ]. This discrepancy could be because the former study used male faces as stimuli, and there is some evidence that at least in youth, males show greater fear acquisition and decreased fear extinction learning in response to male faces [ 31 ]. Li and Graham did however show that women with high estradiol displayed greater CS− expectancies during early extinction trials, and hormonal contraceptive users displayed lower expectancy ratings to the safety signal than did men during fear extinction [ 32 ].…”
Section: Gonadal Hormone Effects In Community Samplesmentioning
confidence: 99%